2015
DOI: 10.1007/s11356-015-4937-1
|View full text |Cite
|
Sign up to set email alerts
|

Biosurfactant production by Pseudomonas aeruginosa DSVP20 isolated from petroleum hydrocarbon-contaminated soil and its physicochemical characterization

Abstract: Among 348 microbial strains isolated from petroleum hydrocarbon-contaminated soil, five were selected for their ability to produce biosurfactant based on battery of screening assay including hemolytic activity, surface tension reduction, drop collapse assay, emulsification activity, and cell surface hydrophobicity studies. Of these, bacterial isolate DSVP20 was identified as Pseudomonas aeruginosa (NCBI GenBank accession no. GQ865644) based on biochemical characterization and the 16S rDNA analysis, and it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 41 publications
3
13
0
2
Order By: Relevance
“…In 13 C NMR, signals between 10.0 and 40.0 ppm were ascribed to aliphatic groups; between 68 and 80 ppm were due to carbon atoms in rhamnose moiety; and signals at 170–175 ppm were attributed to the carbonyl groups (Silva et al 2014 ). Taken together, 1 H and 13 C NMR spectra obtained proved the presence of RLs in the mixture and the spectra coincided with previously published RLs spectra for both 1 H NMR (Charles Oluwaseun et al 2017 ; Raza et al 2009 ; Sharma et al 2015 ) and 13 C NMR (Charles Oluwaseun et al 2017 ; Silva et al 2014 ; Twigg et al 2018 ). Since the precise RLs structure was unachievable using NMR, further characterization using HPLC-MS was carried out.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In 13 C NMR, signals between 10.0 and 40.0 ppm were ascribed to aliphatic groups; between 68 and 80 ppm were due to carbon atoms in rhamnose moiety; and signals at 170–175 ppm were attributed to the carbonyl groups (Silva et al 2014 ). Taken together, 1 H and 13 C NMR spectra obtained proved the presence of RLs in the mixture and the spectra coincided with previously published RLs spectra for both 1 H NMR (Charles Oluwaseun et al 2017 ; Raza et al 2009 ; Sharma et al 2015 ) and 13 C NMR (Charles Oluwaseun et al 2017 ; Silva et al 2014 ; Twigg et al 2018 ). Since the precise RLs structure was unachievable using NMR, further characterization using HPLC-MS was carried out.…”
Section: Discussionsupporting
confidence: 90%
“…1 . Data from previous studies was used to assign the NMR signals as shown in Table 1 (Nicolo et al 2017 ; Sharma et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, economic carbon sources such as wastes and renewable substrates [ 3 ] can be used to replace some conventional substrates. These include mannitol [ 33 ], glucose, glycerol, n -paraffin [ 34 , 35 ], n -alkane, polycyclic aromatic hydrocarbons [ 36 ] and vegetable oils [ 37 ]. The diversity of renewable resources that can be used as carbon and nitrogen sources for rhamnolipid fermentation with reduced substrate cost are discussed in detail in several recent reviews [ 3 , 38 40 ].…”
Section: Strategies To Reduce Production Costmentioning
confidence: 99%
“…Biosurfactant producers mostly exist in oil contaminated soils, where they are able to facilitate the uptake of hydrocarbons through the formation and release of surface active molecules (Chen et al, 2012). There are many reports about the isolation of Bacillus and Pseudomonas species as biosurfactant producers from oilcontaminated areas (Chandankere et al, 2013;Sharma et al, 2015). However, such ability in the genus of Acinetobacter has been seldom described.…”
Section: Introductionmentioning
confidence: 99%